Computed Tomography and Magnetic Resonance Imaging Findings in a Case with Biliary Microhamartomas. (31st January 2012) - Dilli, Alper; Ayaz, Umit Yasar; Yüksel, Ilhami; Damar, Cagrı; Ayaz, Sevin; Hekimoglu, Baki
Abstract : Biliary microhamartomas, also known as bile duct hamartomas and von Meyenburg complexes, are benign neoplasms containing cystic dilated bile ducts embedded in fibrous stroma. They develop in hepatobiliary system, do not generally give clinical outcomes, and are detected incidentally. However, they can rarely show malignant transformation. Our aim was to report the contribution of computed tomography, routine magnetic resonance imaging, and magnetic resonance cholangiopancreatography in the diagnosis of biliary microhamartomas in a 61-year-old woman.